2019
DOI: 10.48550/arxiv.1902.03742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetization process of the insulating ferromagnetic semiconductor (Al,Fe)Sb

Shoya Sakamoto,
Le Duc Anh,
Pham Nam Hai
et al.

Abstract: We have studied the magnetization process of the new insulating ferromagnetic semiconductor (Al,Fe)Sb by means of x-ray magnetic circular dichroism. For an optimally doped sample with 10% Fe, a magnetization was found to rapidly increase at low magnetic fields and to saturate at high magnetic fields at room temperature, well above the Curie temperature of 40 K. We attribute this behavior to the existence of nanoscale Fe-rich ferromagnetic domains acting as superparamagnets. By fitting the magnetization curves … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Considering the low concentrations of Fe atoms doped into the host semiconductors, it appears necessary to think about the inhomogeneous distribution of Fe atoms on the nanoscale, or the spinodal nanodecomposition [6], because both superexchange and double-exchange interactions are short-ranged. In fact, previous XMCD measurements on (In,Fe)As:Be [30] and (Al,Fe)Sb [38] thin films grown by the molecular beam epitaxy methods revealed that there exist nanoscale ferromagnetic domains even at room temperature much above the macroscopic T C , the origin of which was attributed to the nanoscale Fe concentration fluctuation. Furthermore, the nanoscale Fe-rich lamellae-like structures were recently observed in (In,Fe)As thin films prepared by the pulsed laser melting method [39].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the low concentrations of Fe atoms doped into the host semiconductors, it appears necessary to think about the inhomogeneous distribution of Fe atoms on the nanoscale, or the spinodal nanodecomposition [6], because both superexchange and double-exchange interactions are short-ranged. In fact, previous XMCD measurements on (In,Fe)As:Be [30] and (Al,Fe)Sb [38] thin films grown by the molecular beam epitaxy methods revealed that there exist nanoscale ferromagnetic domains even at room temperature much above the macroscopic T C , the origin of which was attributed to the nanoscale Fe concentration fluctuation. Furthermore, the nanoscale Fe-rich lamellae-like structures were recently observed in (In,Fe)As thin films prepared by the pulsed laser melting method [39].…”
Section: Discussionmentioning
confidence: 99%